Comparison of the Shear Bond Strength of Orthodontic Composites Containing Silver and Amorphous Tricalcium Phosphate Nanoparticles: an ex vivo Study - Zahra Tavakolinejad; Yasaman Mohammadi Kamalabadi; Arman Salehi (Shiraz University of Medical Sciences, 2023)
Statement of the Problem: It is important to use orthodontic composites with favorable properties, which are easily removed after the end of the treatment but not easily debonded during treatment. Nanoparticles have drawn attention for their antibacterial properties when added to composite resins. However, the effect of addition of nanoparticle on shear bond strength is not broadly discussed.Purpose: The present study was designed to compare the shear bond strength of orthodontic brackets bonded by orthodontic composite containing silver nanoparticles with orthodontic composite containing amorphous tricalcium phosphate nanoparticles.Materials and Method: In this ex vivo study, 36 sound extracted human premolars were used and randomly divided into three groups. The brackets were bonded in the first group by composite without nanoparticles, in the second group by composite containing 3% amorphous tricalcium phosphate nanoparticles and in the third group by composite containing 0.3% silver nanoparticles at the buccal surface of the teeth. The shear bond strengths of the samples were measured 24 hours after preparation by a universal testing machine. Data were analyzed using SPSS 21 software through one-way ANOVA and Tamhane's T2 multiple comparison tests. p Values under 0.05 were considered significant.Results: There was no significant difference between the mean shear bond strength of composite containing amorphous tricalcium phosphate nanoparticles with composite without nanoparticles (p= 0.142). However, the mean shear bond strength in the composite containing silver nanoparticles was significantly lower than the other two groups (p<  0.001).Conclusion: According to the results of this study, the addition of amorphous tricalcium phosphate nanoparticles to orthodontic composite does not significantly decrease the shear bond strength while silver nanoparticles reduce the shear bond strength of orthodontic composite.